Cognitive impairment in Aboriginal people with heavy episodic patterns of alcohol use. - Cairney S; Clough A; Jaragba M; Maruff P (Addiction, 2007)
BACKGROUND: With chronic alcohol abuse, cognitive studies suggest that progressive cognitive decline may precede more serious and irreversible neurological syndromes. The early detection of cognitive impairment may therefore aid in the prevention of permanent brain damage. Despite the devastating consequences of alcohol abuse among Aboriginal Australians, the effects on brain function have never been studied in this population and a lack of appropriate assessment tools has prevented the development of such research. AIMS: To determine the impact of long-term and heavy episodic alcohol use on cognitive function in Aboriginal people. DESIGN: Cross-sectional comparing heavy episodic alcohol users with non-alcohol users. SETTING: Two remote Aboriginal communities in north-east Arnhem Land, northern Australia. SUBJECTS: The control group consisted of 24 non-drinkers (15 males, nine female) and the heavy episodic group consisted of 20 people (19 males, one female) who had been drinking alcohol in a heavy episodic style (median 14 drinks per occasion) for a mean of 8.9 years (SD = 5.0). MEASUREMENTS: Interview to obtain demographic information, substance abuse history and symptoms of mental health and wellbeing, together with a computerized cognitive assessment battery (CogState Ltd). FINDINGS: Compared with non-drinkers, heavy episodic drinkers showed reduced psychomotor speed (P = 0.04) and reduced accuracy when performing tasks of attention (P = 0.045), working memory (P = 0.04), implicit memory (P = 0.03) and associate learning and memory (P = 0.001). CONCLUSIONS: Specific cognitive abnormalities that suggest frontostriatal abnormalities and have been observed in association with chronic alcoholism in other populations were observed among Aboriginal Australians who were heavy episodic alcoholic users.